Characterization of ancient Korean pigments by surface analytical techniques - Kim, Minjung; Lee, Jihye; Doh, Jung-Mann; Ahn, Heesook; Kim, Hae Dong; Yang, Yimin; Lee, Yeonhee (WILEY, 2016)
The identification of pigments applied in ancient paintings is of great importance for art conservation and history. In this work, pigment samples from the 19th century Korean Buddhist painting (taenghwa) at the Hwangnyongsa temple were analyzed using two analytical techniques: portable X-ray fluorescence (XRF) and time-of-flight secondary ion mass spectrometry (ToF-SIMS). Portable XRF was used to obtain elemental information about the pigments applied in the Korean guardian Buddhist painting. The XRF results revealed the characteristic elements in the pigments that were commonly used in that period. The qualitative and non-destructive XRF analyses of pigment layers of the Buddhist painting were compared with results obtained using the micro-destructive ToF-SIMS technique. The ToF-SIMS spectra of the pigments showed characteristic elemental peaks such as Pb+, Cu+, Hg+, Al+, and hydrocarbon ions for the white, green, red, blue, and black areas in the positive ion mode and CO3-, OH-, S-, Cl-, and CnH- in the negative ion mode, respectively. The XRF and ToF-SIMS results show that the white, green, and red areas in the Buddhist painting were painted with lead white, malachite, atacamite, cinnabar, and mars red as single or mixed pigments. Smalt and carbon were used to depict the blue and black areas in the Buddhist painting, respectively. ToF-SIMS combined with complementary methods such as portable XRF provides important information about ancient painting materials on a sub-micrometer scale. Therefore, by combining these complementary techniques, a thorough characterization of each pigment can be obtained, allowing for a proper strategy for the restoration process. Copyright (c) 2016 John Wiley & Sons, Ltd.
Keywords: ION MASS-SPECTROMETRY; WALL PAINTINGS; GREEN PIGMENTS; RAMAN; IDENTIFICATION; ART; CERAMICS; SIMS; XRF